Treat-to-target strategy with secukinumab as a first-line biological disease modifying anti-rheumatic drug compared to standard-of-care treatment in patients with active axial spondyloarthritis: protocol for a randomised open-label phase III study, AScalate - Xenofon Baraliakos; Denis Poddubnyy; Ludwig Hammel; Marvin Heyne; Justyna Veit; Claudia Jentzsch (BMJ Open)
Introduction In patients with axial spondyloarthritis (axSpA), biological disease-modifying anti-rheumatic drugs (bDMARDs) are recommended to those with inadequate response or contraindications to non-steroidal anti-inflammatory drugs (NSAIDs). In case of failure of the first bDMARD, a switch within the class or to other bDMARD is recommended. Despite these treatment options, there is no optimal treat-to-target (T2T) strategy. This study aims to evaluate the efficacy of a T2T strategy in patients with axSpA, with secukinumab as a first-line bDMARD, compared with standard-of-care (SOC) treatment.Methods and analyses This is a randomised, parallel-group, open-label, multicentre ongoing study in patients with axSpA who are naïve to bDMARD and who have had an inadequate response to NSAIDs. The study will include an 8-week screening period, a 36-week treatment period and a 20-week safety follow-up period. At baseline, patients will be randomised (1:1) to T2T or SOC group. In the T2T group, patients will be treated with secukinumab 150 mg subcutaneous (s.c.) weekly until week 4 and then at week 8. For non-responders (patients without Ankylosing Spondylitis Disease Activity Score [ASDAS] clinically important improvement; change from baseline ≥1.1) at week 12, dose will be escalated to 300 mg s.c. every 4 weeks until week 24. Non-responders at week 24 will be switched to adalimumab biosimilar 40 mg s.c. every 2 weeks until week 34. In the SOC group, patients will receive treatment at the discretion of the physician. The primary endpoint is the proportion of patients achieving an Assessment in SpondyloArthritis International Society 40% (ASAS40) response at week 24.Ethics and dissemination The study is being conducted as per the ethical principles of the Declaration of Helsinki and after approval from independent ethics committees/institutional review boards. The first results are expected to be published in early 2022.Trial registration number This study is registered with ClinicalTrials.gov, NCT03906136.